Pengaruh Karakteristik Individu dan Faktor Ekstrinsik terhadap Kinerja Bidan - Linda, Herna; Zulfendri, Zulfendri; Juanita, Juanita (Jurnal Samudra Ekonomi dan Bisnis, 2021)
The performance of the midwife as part of the human resources owned by the hospital will affect the performance of the health service institution concerned as a whole. The purpose of this study was to analyze the effect of individual characteristics (including age, years of service, employment status, skills, and motivation) and extrinsic factors (including rewards, workload, supervision, and training) on the performance of midwives. This explanatory survey research used all of the midwives who served in the inpatient obstetrics room at Langsa Hospital, amounting to 47 people as respondents. Data were collected through questionnaires and analyzed by logistic regression method. The results showed that employment status, skills and motivation from individual characteristics as well as supervision and training from extrinsic factors had a significant effect on the performance of midwives. Furthermore, motivation was identified as the dominant variable influencing the performance of midwives.